On the Use of Thermoelectric Devices in Cryosurgery - Moskalyk, I.A. (Physics and Chemistry of Solid State, 2015)
In this article the current state of thermoelectric devices usage in cryosurgery is given. The advantages of thermoelectric cooling devices and rational spheres of their application are determined.